A systematic review of health-related quality of life outcomes in patients with advanced breast cancer treated with palbociclib - Imtiaz A Samjoo; Alexandra Hall; Connie Chen; Bao-Ngoc Nguye; Meaghan Bartlett; Mary Lou Smith; Nadia Harbeck; Joseph C Cappelleri; Meghan Karuturi; Doris Makari; Lillian Shahied Arruda; Rickard Sandin; et al. (Becaris Publishing Limited, 2024)
Aim: To evaluate the impact of palbociclib treatment on health-related quality of life (HRQoL) in patients with hormone receptor-positive, human epidermal growth factor 2-negative advanced breast cancer (HR+/HER2- aBC) or metastatic breast cancer (mBC) in both the clinical and real-world setting. Materials & methods: A systematic literature review was conducted to identify clinical trials and real-world evidence studies up to June 2023 that reported HRQoL outcomes in patients with HR+/HER2- aBC or mBC treated with Palbociclib. Results: 15 unique studies reported across 35 records were identified. Of these, seven were randomized controlled trials (RCTs), three were single-arm clinical trials and five were real-world evidence (RWE) studies. HRQoL was generally found to be maintained in patients with HR+/HER2- aBC or mBC across RCTs, single-arm clinical trials and RWE studies. HRQoL measures across instruments, study types and line of therapy, were largely reported to be at least maintained if not improved from baseline among patients treated with palbociclib and were observed to be comparable or better in the palbociclib group versus monotherapy control arm in RCTs. Similar results were seen for treatment related outcomes (e.g., sexual functioning, upset by hair loss, systemic therapy side effects etc.), and important individual patient outcomes, including pain, fatigue and physical functioning. Findings were also consistent across key clinical characteristics (visceral metastases, neutropenia), as well as patient populations often underrepresented in clinical trials (Asian patients, older adults). Conclusion: Overall, current evidence suggests that HRQoL is largely preserved with the addition of palbociclib to endocrine therapy in patients with HR+/HER2- aBC or mBC across study types and populations.